Would Chrysomya albiceps (Diptera: Calliphoridae) be a beneficial species? - Madeira, N.G. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2001)
Chrysomya albiceps (Widemann) é uma mosca que se desenvolve em carcaças e opcionalmente pode causar miíase secundária. Larvas de segundo estádio foram removidas de uma lesão existente em uma ovelha da raça Merino em Botucatu. Entre a lã, ao redor da lesão, foram encontradas larvas de primeiro estádio. Também no interior da lesão foi obtida uma larva de terceiro estádio. As larvas foram mantidas em laboratório e delas obtidos insetos adultos, com 50 casais formados e mantidos em gaiolas por oito gerações. de cada geração, 100 adultos eram sacrificados e examinados morfologicamente, com os seus caracteres confrontados com os de Chrysomya rufifacies. A larva de terceiro estádio deu origem a Cochliomyia hominivorax e as demais a C. albiceps. Foi verificado que C. albiceps, além de ser capaz de danificar tecido integro, é também uma possível predadora de larvas de C. hominivorax. A importância de C. albiceps para os animais domésticos e sua associação com C. hominivorax é aqui discutida.

Chrysomya albiceps (Widemann) develops on animal carcasses and may cause secondary myiases. An adult female Merino sheep presented a lesion of roughly circular shape with a 7.5cm radius in the anterior part of the thorax. A large number of second-instar larvae was removed from the lesion in addition to first-instar larvae from the wool. A third-instar larva was also obtained from the same lesion site and in the laboratory gave origin to a Cochliomyia hominivorax (Coquerel) adult insect. The larvae retrieved from the lesion were nurtured in laboratory. Pairs consisting of 100 individuals were formed with the adult specimens obtained from the larvae and kept in two cages. In all of the 800 adults reared in the laboratory and examined (100 per generation) the propisternal seta was absent in the spiracle on both sides, this trait was highly stable. The 200 larvae examined, 15 per generation, did not present spines in the column of the ventral process of the penultimate abdominal segment and the column of the ventral process was triangular and the apex of the column process presented numerous spines. These characteristics allowed identifying these specimens as C. albiceps. However, since C. albiceps has the ability to damage intact tissues, it may be causing relevant aggravation when associated with C. hominivorax and can not be considered innocuous.
Seria Chrysomya albiceps (Diptera: Calliphoridae) uma espécie benéfica?
Keywords: Chrysomya albiceps; miíase; associação de espécies; Diptera; Chrysomya albiceps; myiasis; species associations; Diptera